Minimizing Disguised Equity as Mandated by the Income Tax Law of Indonesia - Setiawan, Widy (Jambura Equilibrium Journal, 2024)
The Indonesian government has limited the Debt-to-Equity Ratio (DER) to a maximum of 4:1 since the 2016 tax year and reduced the corporate income tax rate from 25% to 22% since the 2020 tax year. I compared data on public companies in Indonesia and Thailand to see the impact of reducing tax rates to reduce Tax Avoidance and reduce Disguised Equity. I also analyzed the findings of eleven previous studies regarding the effectiveness of DER restrictions in Reducing Tax Avoidance and Disguised Equity. As a result, a decrease in the tax rate has not been correlated with tax avoidance and DER. DER restrictions, although effective in reducing Disguised Equity, are ineffective in boosting tax revenues through company capital structure changes because with a DER limit of 4:1, companies still have room for tax savings. The DER limit of 4:1 is still higher than the average DER in sample companies of 0.3:1. Therefore, I suggest that the government immediately implement interest cost limitation regulations with the Interest Expense Limitation Based on EBITDA provisions as recommended by the OECD. I simulated changes in interest cost financing restrictions for companies listed on the Indonesia Stock Exchange between 2016 and 2021 if using a DER limit of 4:1 and if using Interest Expense Limitation Based on EBITDA. As a result, the government can increase potential tax revenues significantly.